Guardian of the presidency the legacy of Richard E. Neustadt - Dickinson, Matthew J.; Neustadt, Elizabeth A.; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2007)
"Richard Neustadt's former colleagues and students celebrate the rich and diverse contributions he made to political and academic life in the United States and beyond"--Provided by publisher.
Foreword / Doris Kearns Goodwin -- Preface -- "Placing" Richard E. Neustadt / Ernest R. May -- Practicum on the presidency, 1946 to 1953 / Matthew Dickinson -- Scholar-activist as guardian : Dick Neustadt's presidency / Charles O. Jones -- Avoiding the hazards of transition : Neustadt's lessons / Harrison Wellford -- Two of JFK's aides remember Kennedy's Machiavelli / Theodore C. Sorenson and Arthur Schlesinger, Jr. -- An American in England / Anthony King -- Was Neustadt a journalist, too? / Jonathan Alter -- Tribute to a teacher / Al Gore -- Masterful mentor / Harvey V. Fineberg -- Institution builder / Graham Allison -- Neustadt in Brazil / Eric Redman -- Afterword : a personal reminiscence / Elizabeth A. Neustadt -- Appendix : Letter to Helena Kerr do Amaral, June 15, 2003 -- Letter to President Lyndon B. Johnson, January 13, 1968, with attachment -- Memorandum to Lyndon B. Johnson from John P. Roche, January 18, 1968.
Includes bibliographical references (p. 205-207) and index.
Electronic reproduction.
Keywords: Neustadt, Richard E; Harvard University -- Faculty -- Biography; Political consultants -- United States -- Biography; Political scientists -- United States -- Biography; Electronic books